How modes of instrumental practice are distributed in three musical genres and among vocalists and instrumentalists at music colleges. (September 2019) - Sandgren, Maria
The present study investigates whether past and present instrumental practices differ across musical genres (jazz, folk music, classical music) and vocalists in relation to instrumentalists ( N = 108). New findings were that vocalists and instrumentalists differed significantly in all practice experiences ( p < .05–.001), whereas fewer differences were found across genres. In line with previous research, classical musicians engaged more in solitary practice than folk music and jazz musicians did ( p < .001), yet jazz and folk music students practiced more in ensemble compared to classical musicians ( p < .05). In addition, the results contrasted with the general view of solitary practice as a demanding and unpleasant activity, as all groups of music students found solitary practice to be a more positive than negative experience. Future studies are warranted to more closely and empirically investigate vocalists' practice habits, and to examine how emotions are related to instrumental practicing in music education.